Exploration Of Antidiabetic Potentials Of Eurycoma Longifolia Plant Extract - Lakshita, Lakshita; Jalwal, Pawan; Shailja, Shailja (Journal of Neonatal Surgery, 2025)
Eurycoma longifolia, commonly known as Tongkat Ali, is a flowering plant from the Simaroubaceae family, widely recognized for its medicinal and therapeutic properties. This study focuses on the morphological characteristics, phytochemical composition, and pharmacological potential of E. longifolia. Morphological analysis revealed that the plant grows as a slender shrub or small tree, reaching heights of up to 10 meters (32.8 feet), with compound leaves arranged in a spiraled pattern. The flowers are small, reddish-brown, and borne in clusters, while the roots are long and fibrous, often used in traditional medicine. The taste of the root extract is intensely bitter. Eurycoma longifolia is rich in bioactive compounds such as quassinoids, alkaloids, and flavonoids, contributing to its anti-inflammatory, aphrodisiac, and adaptogenic properties. Traditionally, it has been used for enhancing male fertility, improving energy levels, and managing stress. The plant thrives in tropical rainforests with well-drained soils, making it an essential medicinal resource in Southeast Asian herbal medicine. This research highlights the morphological attributes, phytochemical potential, and pharmacological significance of E. longifolia, supporting its traditional and emerging applications in natural medicine and health supplements.